Alien fish shift the biomass distribution towards a bottom-heavy pyramid in the Pearl River Basin, China - Yuguo Xia; Yuefei Li; Shuli Zhu; Xinhui Li; Yuxin Zhang; Jie Li (Ecological Indicators)
The effects of biological invasion on aquatic ecosystems have been widely evaluated, with varying effects at the population and food web levels. However, the effects of invasive alien fish on trophic cascades, biomass distribution, and population dynamics are poorly understood, leading to poor ecosystem management. In this study, we quantified the trophic disruptions attributable to alien fish by investigating changes in the biomass structure of a food web pyramid. Using a 3-year catch dataset from the Pearl River Basin in China, we employed Bayesian mixed-effects models, a piecewise structural equation model, and Pearson’s correlation analysis to explore alien fish effects and trophic interactions in food webs. Our results indicated that invasive alien fish lead to a downward shift in the food web. The alien fish did not affect the total catch per unit effort (CPUE) but significantly decreased the mean trophic level. Trophic interactions were primarily controlled by bottom-up forces in the invaded ecosystem. Moreover, biomass compensation effects were observed between the alien and native species. Invasion did not considerably affect the biomass structure but shifted the biomass distribution towards a more traditional bottom-heavy pyramid. Our results highlight the importance of managing invasive alien species at the ecosystem level and that biomass compensation could be considered for controlling invasive populations.